Identification of Genetic Features for Attenuation of Two Salmonella Enteritidis Vaccine Strains and Differentiation of These From Wildtype Isolates Using Whole Genome Sequencing - Tang, Yue; Davies, Rob; Petrovska, Liljana (Frontiers in Veterinary Science, 2019)
Salmonella Enteritidis is a leading cause of salmonellosis worldwide and more than 80% of outbreaks investigated in Europe have been related to the consumption of insufficiently cooked eggs or foods containing raw eggs. Vaccination has been shown to be one of the most important measures to control Salmonella Enteritidis infections in poultry farms as it can reduce colonization of the reproductive organs and intestinal tract of laying hens, thereby reducing egg contamination. Differentiation of live vaccine from field or wild type S. Enteritidis isolates in poultry is essential for monitoring of veterinary isolates and targetting control actions. Due to decreasing costs, whole genome sequencing (WGS) is becoming a primary tool for chracteristion of Salmonella isolates, including vaccine strains. Using WGS we described the genetic changes in the live attenuated Salmovac 440 and AviPro SALMONELLA VAC E vaccine strains and compared with wildtype S. Enteritidis. SNP analysis confirmed that streptomycin resistance was associated with a Lys43Arg missense mutation in the rpsL gene whilst 3 missense mutions in acrB and 1 missense mutation in acrA confer erythromycin sensitivity in AviPro SALMONELLA VAC E. Further mutations Arg242His in purK and Gly236Arg in the hisB gene were related to adenine and histidine dependencies in Salmovac 440. Unique SNPs were used to construct a database of variants for differentiation of vaccine from the wildtype isolates. Two fragments from each vaccine were represented in the database to ensure high accuracy. Each of the two selected Salmovac 440 fragments differed by 6 SNPs from the wildtype and the AviPro SALMONELLA VAC E fragments differed by 4 and 6 SNPs respectively. CD-hit software was applied to cluster similar fragments that produced the best fit output when searched with SRST2. We tested the vaccine differentiation method with 1253 genome samples including field isolates of Salmovac 440 (n=51), field isolates of AviPro SALMONELLA VAC E (n=13), S. Gallinarum (n=19), S. Pullorum (n=116), S. Enteritidis (n=244), S. Typhimurium (n=810) and achieved 100% sensitivity and specificity.